2023
DOI: 10.1021/acsami.3c08377
|View full text |Cite
|
Sign up to set email alerts
|

Indispensable Nafion Ionomer for High-Efficiency and Stable Oxygen Evolution Reaction in Alkaline Media

Nitul Kakati,
Lawrence Anderson,
Guangfu Li
et al.

Abstract: Addressing the challenge of sluggish kinetics and limited stability in alkaline oxygen evolution reactions, recent exploration of novel electrochemical catalysts offers improved prospects. To expedite the assessment of these catalysts, a half-cell rotating disk electrode is often favored for its simplicity. However, the actual catalyst performance strongly depends on the fabricated catalyst layers, which encounter mass transport overpotentials. We systematically investigate the role and sequence of electrode d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…109 Naon acts as an effective binder and further improves the interfacial interaction between electrolyte and catalyst, improving stability and performance by up to 20% compared to Naon-free catalyst layers. 110 Lan et al synthesised a Mo-doped Ni 3 S 2 nanocluster array applied to NF (Mo-Ni 3 S 2 /NF), where the catalyst is prepared using a single-step modied solvothermal methodology using thiourea as the sulphur source at 160 °C for 6 hours. 106 The introduction of Mo progresses the nickel and S organisation, improving electronic interactions and increasing OER reaction kinetics and long-term stability, according to the authors.…”
Section: Modication Techniquesmentioning
confidence: 99%
“…109 Naon acts as an effective binder and further improves the interfacial interaction between electrolyte and catalyst, improving stability and performance by up to 20% compared to Naon-free catalyst layers. 110 Lan et al synthesised a Mo-doped Ni 3 S 2 nanocluster array applied to NF (Mo-Ni 3 S 2 /NF), where the catalyst is prepared using a single-step modied solvothermal methodology using thiourea as the sulphur source at 160 °C for 6 hours. 106 The introduction of Mo progresses the nickel and S organisation, improving electronic interactions and increasing OER reaction kinetics and long-term stability, according to the authors.…”
Section: Modication Techniquesmentioning
confidence: 99%
“…Recent works from Zhang et al and Boutin et al have shown that cobalt phthalocyanine (CoPc) supported on multiwalled-carbon nanotubes (MWCNT) is an excellent hybrid electrode for CO 2 reduction. , In these articles, the researchers used Nafion, a branched fluoropolymer ionomer with pendent terminal sulfonate groups, as a binding agent to keep the MWCNT and CoPc from delaminating from the electrode by providing mechanical strength. ,, Also, ionomers like Nafion are commonly used in the fuel cell field as dispersants stabilizing catalyst inks . At low loadings, ionomers have been shown to be beneficial to the electrode by providing a higher ionic conductivity, and a degree of control of wettability and aggregate size. At high ionomer loadings >30 wt %, there can be negative consequences such as capacitive charging, and a decrease in reactant mass transport to the catalyst. , The introduction of these ionomers will also inherently alter the microenvironment of the catalyst site as addition of Nafion has been found to affect local pH and local structural morphology changes via solvent dependence. , Sharma et al observed in their CO 2 reduction system a decrease in CO selectivity and active catalyst as Nafion loading increased up to 30 wt % . Of particular interest is the nature of interaction between the immobilized catalysts and their graphitic supports .…”
Section: Introductionmentioning
confidence: 99%
“…1(b) displays this scenario for a hypothetical carbon nanomaterial decorated with a precious metal nanoparticles, and dropcast with Nafion ionomer to serve as a physical binder to improve the dispersion and stability of the layer. 19 …”
Section: Introductionmentioning
confidence: 99%